2005
DOI: 10.1164/rccm.200403-406oc
|View full text |Cite
|
Sign up to set email alerts
|

Agonists of Toll-like Receptors 2 and 4 Activate Airway Smooth Muscle via Mononuclear Leukocytes

Abstract: These data indicate that potent amplification of inflammation induced by TLR agonists, such as LPS, may be achieved by cooperativity between airway smooth muscle and leukocytes involved in immune surveillance or inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
109
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 56 publications
12
109
0
Order By: Relevance
“…LPS exposure induced increased diffuse expression in multiple cell types in the lung. Similar diffuse localization has been shown in the adult human lung (23,26,27). The resolution of in situ hybridization does not allow for localization of the signal to specific cells.…”
Section: Discussionmentioning
confidence: 64%
“…LPS exposure induced increased diffuse expression in multiple cell types in the lung. Similar diffuse localization has been shown in the adult human lung (23,26,27). The resolution of in situ hybridization does not allow for localization of the signal to specific cells.…”
Section: Discussionmentioning
confidence: 64%
“…Generally, expression of PRRs by immune cells such as M1 macrophages serves a protective role following infection. Structural cells such as type II alveolar epithelial cells (47), airway smooth muscle cells (48), airway epithelial cells (49), and fibroblasts express TLRs, including TLR2, TLR3, TLR4, and TLR9, and are activated by specific TLR ligands. Less is known about the expression and activation of other PRRs in these cell types.…”
Section: From Pathogens To the Chronic Inflammatory Response And Pathmentioning
confidence: 99%
“…Furthermore, urban particulate matter has been shown to cause the release of monocytes from the bone marrow (17, 23). We have previously shown that effective inflammatory responses to bacterial-derived stimuli are mediated by cooperative signaling between monocytes and tissue cells (31,32,39,50). The direct effects of DEP, with the production of proinflammatory cytokines and ROS in single cell types, are well established (4,9,25,27,29,37,43,49), but less is known about their actions in models of the cell networks that underpin inflammatory responses.…”
mentioning
confidence: 99%